Penalidad salarial por maternidad: Análisis del efecto de los hijos sobre los ingresos laborales de las mujeres bolivianas del área urbana - Erka Tatiana Soliz Cuevas (Universidad Católica Boliviana, Instituto de Investigaciones Socio-Económicas (IISEC), 2022)
– The economic literature that studies the salary gaps between men and women produced by children. However, there may also be wage gaps between women with children and women without children, which is known as a motherhood wage penalty and whose study for countries such as Bolivia is scarce. Therefore, this paper aims to assess the wage penalty for maternity for Bolivian women in urban areas. For this, estimates of wage equations are used, taking into account a selection bias correction. The results show that when the penalty is evaluated when using a dichotomous variable of maternity condition, there is a penalty and when correcting for selection bias it persists. When evaluating by number of children, it is observed that regardless of the number of children, there is a penalty, but that it is greater when the woman has one child.
Keywords: C24; J13; J16; J31; 330; Motherhood Wage Penalty; Children; Wage Differentials; Selection Bias